The CONSERT operations planning process for the Rosetta mission. (August 2016) - Rogez, Yves; Puget, Pascal; Zine, Sonia; Hérique, Alain; Kofman, Wlodek; Altobelli, Nicolas; Ashman, Mike; Barthélémy, Maud; Biele, Jens; Blazquez, Alejandro; Casas, Carlos M.; Sitjà, Marc Costa; et al.
Abstract: The COmet Nucleus Sounding Experiment by Radio wave Transmission (CONSERT / Rosetta) has been designed to sound the interior of the comet 67P/Churyumov-Gerasimenko. This instrument consists of two parts: one onboard Rosetta and the other one onboard Philae. A good CONSERT science measurement sequence requires joint operations of both spacecrafts in a relevant geometry. The geometric constraints to be fulfilled involve the position and the orientation of both Rosetta and Philae. At the moment of planning the post-landing and long-term science operations for Rosetta instruments, the actual comet shape and the landing location remained largely unknown. In addition, the necessity of combining operations of Rosetta spacecraft and Philae spacecraft makes the planning process for CONSERT particularly complex. In this paper, we present the specific methods and tools we developed, in close collaboration with the mission and the science operation teams for both Rosetta and Philae, to identify, rank and plan the operations for CONSERT science measurements. The presented methods could be applied to other missions involving joint operations between two platforms, on a complex shaped object. Highlights: We analyze the constraints and requirements for the CONSERT instrument operation. We analyze the Rosetta and Philae combined operation specific complexity. We present a solution for operation planning with large uncertainties on parameters. We present the methods and tools developed to implement this solution.